THE RELATIONSHIP BETWEEN PARENTING STYLE AND LANGUAGE DEVELOPMENT IN PRESCHOOL CHILDREN - Nova Fridalni; Sri Wahyuningsih; Ratna Indah Sari Dewi; Rifdha Wahyuni; Vivin Okta Diati (STIKES Syedza Saintika Padang, 2026)
Language development in preschool children remains an important concern because delays due to suboptimal stimulation and parental communication interaction are still found. Inappropriate parenting styles may affect children’s ability to understand and express language according to their developmental stage. This study aimed to determine the relationship between parenting style and language development in preschool children aged 3–6 years in Surau Gadang Village, working area of Nanggalo Public Health Center, Padang. A quantitative cross sectional design was used. The population consisted of 671 children with a sample of 87 respondents selected using cluster random sampling. The instruments used were the Parenting Style Questionnaire and the Pre-Screening Developmental Questionnaire. Data were analyzed using univariate and bivariate analysis with Fisher’s Exact Test. Results showed that less than half (43.7%) of parents applied permissive parenting and more than half (54.0%) of children had age-appropriate language development. Bivariate analysis showed a significant relationship between parenting style and children’s language development (p-value = 0.037). This study confirms that parenting style plays an important role in preschool children’s language development. Health centers are recommended to improve education regarding parenting style and language development stimulation.Keywords: parenting style; language development; preschool children